ANALYSIS OF FINANCIAL REPORTS IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) CASE STUDY ON BELLA BURHAN PROJECT BUSINESS - Putri, Alpiani Sakinah; Mansur, Fitrini; Hernando, Riski (Jambi Accounting Review (JAR), 2025)
This study was conducted to determine how to prepare the financial report of the Bella Burhan Project Micro, Small and Medium Enterprises (MSMEs) and to determine the conformity of the financial report with the SAK EMKM (Micro, Small and Medium Macro Entity Financial Accounting Standards) which have been set by the Indonesian Institute of Accountants (IAI). In addition, this study also aims to determine what obstacles are experienced by the MSMEs in preparing financial reports. This study uses a descriptive research method with a qualitative approach to describe in detail the financial statements of the Bella Burhan Project MSME. From this research, it is hoped that it will provide knowledge and insight regarding how to prepare financial reports for MSMEs and their compliance with the MSME SAK, and what difficulties are faced by the research objects in preparing financial reports. Based on the results of interviews and analysis of financial report documents from the research object, it is known that the Bella Burhan Project MSME made financial reports from 2023-2024 in the form of a business profit and loss report. From the results of the analysis, the researcher found that this MSME did not yet have complete financial reports and was still not in accordance with the existing SAK EMKM.